Theory and practice of model transformation : 11th International Conference, ICMT 2018, held as part of STAF 2018, Toulouse, France, June 25-26, 2018, Proceedings /: 11th International Conference, ICMT 2018, held as part of STAF 2018, Toulouse, France, June 25-26, 2018, Proceedings. (2018) - Unknown
No abstract available